PENGARUH PENAMBAHAN TEPUNG KACANG MERAH TERHADAP SIFAT KIMIA DAN HEDONIK BERAS ANALOG BERBAHAN DASAR UMBI GANYONG (CannaedulisKer.) - Salma Salsabila; Antonius Hintono; Bhakti Etza Setiani (Jurnal Agrotek Ummat, 2020)
Analog rice is artificial rice product made from non rice raw material which contain nutrients and looks like padi rice. This research using raw material such as umbi ganyong as source of carbohydrates and red bean to improve the nutritional value and appearance of analog rice.  The purpose of this research was to study the concentration effect offered bean flour added into on rice analog made from umbi ganyong (ganyong root) toward water content, raw fiber, protein, and hedonic. The treatments applied were T0 for 0% concentration, T1 for 5% concentration, T2 for 10% concentration, and T3 for 15% concentration. The observed variables were water content, protein, crude fiber, and preference level. The result of the study showed that the addition of red bean flour with various concentrations reveals the difference(p<0,05) in rising water content, crude fiber, protein, and improving taste, texture, and rice analog fluffiness. The outcome of the research point out that the recommendation of red bean flour added into analog rice was at 15% which were resulting in water content 7,76±0,152%, crude fiber of 3,01±0,68%, and protein 7,41±0,038%,